Genital mycoplasmas in women attending the Yaounde University Teaching Hospital, Cameroon - Anna L. Njunda; Dickson S. Nsagha; Jules C.N. Assob; John N. Palle; Henri L. Kamga; Peter F. Nde; Mengang N.C. Ntube; Patrick E. Weledji (AOSIS, 2011)
Genital mycoplasmas are implicated in pelvic inflammatory diseases, puerperal infection, septic abortions, low birth weight, nongonococcal urethritis and prostatitis as well as spontaneous abortion and infertility in women. There is paucity of data on colonisation of genital mycoplasma in women and their drug sensitivity patterns. The aim of our study was to determine the prevalence of genital mycoplasmas (Ureaplasma urealiticum and Mycoplasma hominis) infection and their drug sensitivity patterns in women. A mycofast kit was used for biochemical determination of mycoplasma infection in 100 randomly selected female patients aged 19-57 years, attending the University of Yaoundé Teaching Hospital (UYTH) from March to June 2010. Informed consent was sought and gained before samples were collected. Genital mycoplasmas were found in 65 patients (65%) [95% CI=55.7%-74.3%] and distributed as 41 (41%) [95% CI=31.4%-50.6%] for U. urealiticum and 4 (4%) [95% CI=0.20%-7.8%] for M. hominis while there was co-infection in 20 women (20%) [95% CI=12.16%-27.84%]. In our study, 57 (57%) [95% CI=47.3%- 67%] had other organisms, which included C. albicans (19 [19%]), G. vaginalis (35 [35%]) and T. vaginalis (3 [3%]). Among the 65 women with genital mycoplasma, the highest co-infection was with G. vaginalis (33.8%). Pristinamycine was the most effective antibiotic (92%) and sulfamethoxazole the most resistant (8%) antibiotic to genital mycoplasmas. We concluded that genital mycoplasma is a problem in Cameroon and infected women should be treated together with their partners.